2012
DOI: 10.1080/02687038.2011.629360
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating and disrupting speech perception in word deafness

Abstract: Background: Word deafness is a rare condition where pathologically degraded speech perception results in impaired repetition and comprehension but otherwise intact linguistic skills. Although impaired linguistic systems in aphasias resulting from damage to the neural language system (here termed central impairments), have been consistently shown to be amenable to external influences such as linguistic or contextual information (e.g. cueing effects in naming), it is not known whether similar influences can be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(50 reference statements)
1
3
0
1
Order By: Relevance
“…Woolf concluded that these participants were using meaning to compensate for their impaired speech perception. Rather similar findings are reported by Robson and colleagues (Robson, Davies, Lambon-Ralph & Sage, 2012).…”
Section: Introductionsupporting
confidence: 75%
“…Woolf concluded that these participants were using meaning to compensate for their impaired speech perception. Rather similar findings are reported by Robson and colleagues (Robson, Davies, Lambon-Ralph & Sage, 2012).…”
Section: Introductionsupporting
confidence: 75%
“…posterior superior temporal gyrus) but multimodal impairments when the lesions are larger and encroach on the transmodal areas (e.g. posterior middle temporal and inferior parietal regions: [30,31]).…”
Section: (B) Transmodal Representationmentioning
confidence: 99%
“…R. Soc. B 369: 20120392 comparative studies of chronic Wernicke's aphasia [31,33] which, in addition to a strong modality difference (spoken words , written words , picture comprehension), have found that the patients' multi-modal semantic impairment has the features of semantic aphasia (control deficits) rather than SD (i.e. representational degradation).…”
Section: (B) Transmodal Representationmentioning
confidence: 99%
“…Speech production in verbal auditory agnosia is relatively normal (Table 32.1), although in some cases production is overly loud and has abnormal prosody (e.g., Otsuki et al, 1998;J€ orgens et al, 2008). Speech perception is typically improved by relying on cross-modal information such as lip reading and from "top-down" contextual information (e.g., Saffran et al, 1976;Coslett et al, 1984;Buchtel and Stewart, 1989;Slevc et al, 2011;Robson et al, 2012). Perception is also sometimes improved by dramatically slowing the speech signal (Albert and Bear, 1974;Stefanatos et al, 2005a), perhaps by ameliorating some patients' particular difficulty with rapid temporal aspects of the speech signal (see below).…”
Section: Verbal Auditory Agnosia (Word Deafness)mentioning
confidence: 98%